Popliteal Artery Pseudoaneurysm: Imaging Features - Krishna Kumar M; Lokesh C; Dharan Venkatesh; Senthilnathan V (Asian Journal of Medical Radiological Research, 2022)
Background: The purpose of this article is to review the imaging features of popliteal artery pseudo-aneurysm. Case Report: We report a 42-year-old male patient with a history of previous blunt injury to left knee presenting with intense pain and edema, with hyperemia and localized temperature increase. Doppler ultrasonography revealed a voluminous pseudo-aneurysm of the popliteal artery with a contained rupture, and hematoma involving the popliteal fossa causing compression of the popliteal vein. Multidetector computed tomography (MDCT) angiography verified the pseudo-aneurysm. Popliteal artery pseudo-aneurysms lead to many dreadful conditions if left untreated. Endovascular repair was accomplished with covered stents and the rupture was verified during the procedure. The aneurysm was barred and the signs and symptoms it had caused resolved fully. Conclusion: Doppler ultrasonography, CT angiography and MR angiography may all be precious in the imaging workup of popliteal pseudo-aneurysms. Prompt diagnosis and treatment of popliteal pseudo-aneurysms are necessary to avoid the morbidity and mortality associated with hemorrhage and rupture. Treatment can involve surgical, medical, and endovascular methods.